Modeling Impact Of Animal Farming On Water Quality Of Serin River - Kho,, Chui Ping (Universiti Malaysia Sarawak, 2009)
Serin River is polluted as a result of effluents disharged from pig farms. Wastewaters from animal farming with high contents of organic matter and nutrient had has destructive consequences on river system. Hence, the objectives of this study were to determine water quality of Serin River and to construct QUAL2K model in order to better understanding the water quality issues in Serin River. The calibrated and validated QUAL2K model using field data from January to March 2009 was used to predict the future water quality of Scrin River. Results of analysis indicated that the tributary that received pig farm effluent has significantly higher mean concentration ammonia-nitrogen (NH3-N) of 2.61 mg/L, organic-nitrogen (Org-N) of 0.96 mg/L and total Kjeldahl nitrogen (TKN) of 3.56 mg/L. This tributary also has the highest average value of copper (Cu) and lowest dissolved oxygen (DO) concentrations. Results of prediction indicated BODc and NH3-N concentrations of receiving river and rivers adjacent to or downstreams of it exceeded Class 11 based on INWQS if wastewaters discharged directly into the river without treatment. The recommended maximum permitted values of temperature, pH. BODS and NH3-N were < 50°C. >_ 5, < 100 mg/L and < 2 mg/L respectively. If the treated wastewaters were being discharged into river, BODS and NH3-N concentrations of receiving river and stations adjacent to or downstreams of it were classified into Class Il. The suggested temperature, p11, BODS and NH3-N values were <_ 35°C, ? 5, <_ 100 mg/L and S 5 mg/L respectively. It is recommended that further studies he conducted on assessment of water quality by using such models to ensure long-term sustainability of river.